Efficiency Gains of Photovoltaic System Using Latent Heat Thermal Energy Storage. (March 2017) - Tan, Lippong; Date, Abhijit; Fernandes, Gabriel; Singh, Baljit; Ganguly, Sayantan
Abstract: This paper presents experimental assessments of the thermal and electrical performance of photovoltaic (PV) system by comparing the latent heat-cooled PV panel with the naturally-cooled equivalent. It is commonly known that the energy conversion efficiency of the PV cells declines with the increment of the PV cell temperature, at a typical value of 0.5%/K. Instead of exploring new semi-conducting materials to reduce the temperature-dependent effect, passive cell cooling is an alternative way to improve the PV power outputs. In the experiment, latent heat thermal energy storage was coupled to the rear side of the PV panel to achieve cell cooling passively. The phase change material (PCM) filled in the thermal storage containment (PCMTS) was organic based paraffin wax which has low melting point of 27 ̊C and high latent heat capacity of 184 kJ/kg. To overcome the poor thermal conductivity of the PCM, metallic fins were incorporated in the LHTES to increase the melting rate of the PCM. In addition, studies of the heat transfer performance using different numbers of metallic fins in heat enhanced PCMTS are compared and analysed. The experimental results show that the finned latent heat-cooled PV panel was able to reduce the panel temperature by 15 ̊C compared to the naturally-cooled PV panel. The maximum electrical conversion efficiency improvement of 5.39% was achieved by the proposed passive cooling approach.